Comparison theorems and necessary/sufficient conditions for the existence of nonoscillatory solutions of forced impulsive differential equations with delay - Shao Yuan Huang; Sui Sun Cheng (Український математичний журнал, 2012)
In 1997, A. H. Nasr provided necessary and sufficient conditions for the oscillation of the equation
where η > 0, p, and g are continuous functions on [0,∞) such that p(t) ≥ 0, g(t) ≤ t, g′(t) ≥ α > 0, and lim t→∞ g(t) =∞. It is important to note that the condition g′(t) ≥ α > 0 is required. In the paper, we remove this restriction under the superlinear assumption η > 1. In fact, we can do even better by considering impulsive differential equations with delay and obtain necessary and sufficient conditions for the existence of nonoscillatory solutions and also a comparison theorem that enables us to apply known oscillation results for impulsive equations without forcing terms to get oscillation criteria for the analyzed equations. У 1997 роцi, А. Х. Наср отримав необхiднi та достатнi осциляцiйнi умови для рiвняння
де η>0, p та g — неперервнi функцiї на [0,∞) такi, що p(t)≥0,g(t)≤t,g′(t)≥α>0 та limt→∞g(t)=∞. Слiд зауважити, що необхiдною тут є умова g′(t)≥α>0. У данiй статтi ми усуваємо це обмеження при суперлiнiйному припущеннi η>0. Насправдi, можна отримати навiть кращий результат, розглядаючи iмпульснi диференцiальнi рiвняння з запiзненням, i встановити необхiднi та достатнi умови iснування неосциляцiйних розв’язкiв, а також теорему порiвняння, яка дає змогу застосувати вiдомi осциляцiйнi результати для iмпульсних рiвнянь без збурюючих членiв, щоб отримати осциляцiйнi критерiї для наших рiвнянь.